(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2024)
The aim of this study is to explore the controversies that emerged from the contextual changes in the film adaptation of Dat Rung Phuong Nam (2023). The study addresses three main research questions. First, it analyses how the film’s contextual changes differ from the original novel and how they are received by the viewers and critics. Second, it evaluates the effect of these controversies on the film’s box office performance and critical recognition. Third, it reveals the challenges and opportunities that arise from adapting literary works to the screen, based on the case of Dat Rung Phuong Nam. The study uses a combination of textual analysis, audience reception studies, and industry perspectives to enhance the understanding of the complex dynamics involved in adapting literary masterpieces to the cinematic medium. The study also highlights the nuances of audience engagement and the implications for commercial outcomes and critical reception.